Tanggung Jawab Profesi Notaris Dalam Penerbitan Sukuk Negara atau Surat Berharga Syariah Negara (SBSN) - Astrie Anindya Sasri (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
Sharia financing instruments are experiencing development, one of the products being national sharia securities (SBSN) or sukuk in order to optimize the state revenue and expenditure budget (APBN). There needs to be a supporting professional responsibility, namely a notary. In issuing SBSN, there is a big risk because it involves a large amount of funds, many parties. , and national wealth. The notary is responsible for making an authentic deed that contains a guarantee of security for the parties. This research aims to determine the legal aspects and responsibilities of the notary profession regarding the issuance of SBSN. The research method uses normative juridical research with a statutory research approach. The results of this research show that SBSN is very useful for obtaining APBN infrastructure financing. State sharia securities (SBSN) or sukuk contain legal aspects that are complete enough to guarantee legal certainty. The legal aspects start from the formation of laws, government regulations, DSN-MUI fatwas, and other regulations. The responsibility of the notary profession in issuing SBSN is not directly involved. Notaries in issuing SBSN are responsible for making authentic deeds, especially contracts to ensure they are in accordance with sharia-based rules, providing legal counseling for the parties as a neutral party, legalizing private documents, and being a witness to the notarized agreement for the issuance of SBSN. has been registered with the OJK as a notary in charge of capital markets.